Money - Harrod, Roy. (St. Martin's : Macmillan, 1969)
Account of the nature of money and the development of monetary theory and of modern institutions; for graduate or undergraduate university students.
Includes index
Includes bibliographic references
usc 09/10/18
Loans
Keywords: Money